EVALUASI PELAKSANAAN PROGRAM KELUARGA BERENCANA DAN KESEHATAN REPRODUKSI DI KAMPUNG KB KABUPATEN: STUDI KASUS KECAMATAN - Syahra Sonia Andhiki; Laksono Trisnantoro; Dwi Handono Sulistyo (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2020)
Background: The Kampung KB program since 2016 has made families take the initiative to invite the surrounding environment to participate in fulfilling family planning needs independently. The village KB program builds cross-sectoral collaboration, one of which is fulfilling aspects of family planning with the achievement of longterm contraceptives (MKJP).Objective: This study aims to explore the extent which is the effectiveness of Kampung KB Program was implemented and has an impact on MKJP achievements in Desa Sumberjaya Kecamatan Gondanglegi, Kabupaten Malang.Methods: The approach is a case study using quantitative and qualitative data that will provide information about the context, input, process, and product of family planning targets. Quantitative data were collected from documented secondary data reports. Subjects totalling 22 people are stakeholders involved in implementing family planning policies and program activities. Data were analyzed using content analysis.Results: The implementation of Kampung KB Program in Desa Sumberjaya, Kecamatan Gondanglegi, has been going well in termsof the implementation of POKJA activities, the activity of field line officers, and the availability of contraceptives. In addition, the obstaclesthat need to be addressed are the insufficient distribution of PLKB/Sub PPKBD/cadres in the field, low financial support coupledwith the absence of a strong policy and other challenges that are difficult to penetrate public trust related to MKJP.Conclusion: Aspects that caused MKJP’s achievement have not reached the target in Desa Sumberjaya Kecamatan GondanglegiKabupaten Malang, including the lack of field line officers, minimal operational funding support, less operational policies, and theexistence of a pandemic that caused many activities to be limited and even stopped as well as factors such as the socio-cultural complaints that are complained of difficult for field line officers to penetrate.